Pengaruh Model Pembelajaran Problem based learning (PBL) Terhadap Hasil Belajar Siswa Kelas VIII Pada Materi Sistem Pernapasan Manusia - Kesumawati, Diah; Parinduri, Wina Mariana; Saraan, Zahra Khumayrah (Mahesa Research Center, 2025)
This study focuses on the effect of the problem-based learning (PBL) model on the learning outcomes of eighth-grade students on the subject of the human respiratory system at Mts Al-Washliyah Stabat. The purpose of this study is to determine how the Problem-Based Learning (PBL) model affects the learning outcomes of eighth-grade students at MTS Al-Washliyah Stabat on this subject. The research method used was a quasi-experimental design with a pre-test post-test control group design. This study involved all 132 eighth-grade students. The research sample was determined using purposive sampling, namely class VIII-C as the experimental class (PBL model) and class VIII-D as the control class (lecture method), with a 30-question multiple-choice test instrument, which was analyzed through normality, homogeneity, and independent t-test. The results showed a significant effect on the experimental class with a post-test average score of 84,81 compared to the control class with an average score of 72,09. The hypothesis test obtained a significance value of 0.000 0.05, which means that Ha is accepted, so it can be concluded that the Problem-Based Learning (PBL) model has a positive and significant effect on the learning outcomes of eighth-grade students on the material of the human respiratory system at Mts Al-Washliyah Stabat.